Religiosidad y aprobación católica de la intervención política de la Iglesia Católica y sus líderes en el Perú - Chavez Lazo, Sergio (Pontificia Universidad Católica del Perú, 2019)
Despite the progressive increase in Protestantism, Peru remains one of the countries with the highest percentage of Catholics in Latin America. Due to this, and the degree of legitimacy that it maintains in society, it could be expected that the Catholic Church, its leaders and representatives will have a great political influence in the community that calls itself Catholic, making it relatively easy for them to obtain majority support and consent from this sector. However, the present work suggests that religious affiliation is an insufficient analysis variable to approach the political and mobilizing potential of the Church, its authorities and leaders in Peru. It is argued that, in a context where religious competition has increased, it is necessary to consider at least religiosity as a mediating variable between religious affiliation and the political potential of the Church. Through a quantitative methodology, the sociodemographic profile of each sector of Catholics is described, differentiated according to their self-perception of commitment to religion. In addition, through logistic regression analysis that considers sociodemographic variables, the weight of religiosity in the probability of agreeing with three forms of intervention of the Catholic Church in the political arena is also evaluated. The results indicate that religiosity has a considerable weight in the probability of supporting political interventions by the Church, its authorities and people with strong religious beliefs, allowing a new critical reading to be given to the majority percentage of Catholics in the country.

A pesar del aumento progresivo del protestantismo, el Perú se mantiene como uno de los países con mayor porcentaje de católicos en América Latina. Debido a ello, y al grado de legitimidad que mantiene en la sociedad, se podría esperar que la Iglesia Católica, sus líderes y representantes tengan una gran influencia política en la comunidad que se autodenomina católica, siéndoles relativamente fácil conseguir el apoyo y consentimiento mayoritario de este sector. Sin embargo, el presente trabajo plantea que la afiliación religiosa es una variable de análisis insuficiente para aproximarse al potencial político y movilizador que tienen la Iglesia, sus autoridades y líderes en el Perú. Se argumenta que, en un contexto donde la competencia religiosa ha aumentado, es necesario considerar al menos a la religiosidad como variable mediadora entre afiliación religiosa y potencial político de la Iglesia. A través una metodología cuantitativa se describe el perfil sociodemográfico de cada sector de los católicos, diferenciados según su autopercepción de compromiso con la religión. Además, a través de análisis de regresión logística que considera variables sociodemográficas, se evalúa también el peso que tiene la religiosidad en la probabilidad de estar de acuerdo con tres formas de intervención de la Iglesia Católica en la arena política. Los resultados apuntan que la religiosidad tiene un peso considerable en la probabilidad de apoyar intervenciones políticas de la Iglesia, de sus autoridades y de personas con fuertes creencias religiosas, permitiendo dar una nueva lectura crítica al porcentaje mayoritario de católicos en el país.
Religiosity and Catholic approval of the political intervention of the Catholic Church and its leaders in Peru
Keywords: Religión; https://purl.org/pe-repo/ocde/ford#5.04.01